Indonesian mother’s feeling and thought during pregnancy: a qualitative study - Endang Koni Suryaningsih; Shiang-Feng Wu; Xuan-Yi Yan; Hung-Ru Lin (Journal of Health Technology Assessment in Midwifery, 2018)
During pregnancy, the mother may have a different experience based on many factors. The purpose of this study was to explore the experience of pregnant women in Indonesia. Some studies establish to explore experience during pregnancy in a particular area. However, limit number study underlined the experience in the general area. A descriptive phenomenological study was used to explore the experience of pregnant women during pregnancy. Purposive sampling, one-on-one, in-depth with semi-structural interviews were conducted to collect data. Narratives were analyzed by Colaizzi’s (1978) seven-step method. Data saturation was achieved after interviewing 3 pregnant women. Four themes and the sub-themes were : having feelings (happy for pregnancy coming true and worry about cannot have vaginal delivery), changes in physical condition (evening sickness, appetite changes, difficult sleep, and eating pattern have to change), deal with pregnant physical condition (lying down when vomiting and changing the meals time), ensure pregnancy safety (seeking help from husband, continuous monitoring of fetal head’s position, pay attention to changes in body weight, and pay attention to the data of hemoglobin). This finding presents the evidence for midwives to the importance of understanding the feeling and experience of the mother during pregnancy. Support and attention consider important for mother who experiences CS history and Placenta Previa in the current pregnancy.